2019
DOI: 10.1002/pssa.201900304
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Active Copper–Nickel Complexes in p‐Type Silicon

Abstract: The interaction of substitutional copper atoms (Cus) with interstitial nickel (Nii) or copper (Cui) in crystalline p‐type Si is investigated by DLTS. The mobile interstitial species are introduced at near‐room temperatures by etching in Ni‐ or Cu‐contaminated KOH aqueous solutions. The Cui in‐diffusion is confirmed by the formation of several deep level complexes including the photoluminescence CuPL center which is known to be a Cus atom decorated with three Cui species. The Nii in‐diffusion results in the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…[15] Similarly, Ni s decorated with some other atoms could have donor and acceptor levels close to those of isolated Ni s but no second acceptor level. This hypothesis is in agreement with the observation that the H 80 and E 236 centers are formed not directly but through the intermediate stages, Cu-Ni 160 [7] and E 217 complexes (Figure 3), respectively. In both cases, the sum total of all centers was equal to the initial Cu s concentration.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…[15] Similarly, Ni s decorated with some other atoms could have donor and acceptor levels close to those of isolated Ni s but no second acceptor level. This hypothesis is in agreement with the observation that the H 80 and E 236 centers are formed not directly but through the intermediate stages, Cu-Ni 160 [7] and E 217 complexes (Figure 3), respectively. In both cases, the sum total of all centers was equal to the initial Cu s concentration.…”
Section: Discussionsupporting
confidence: 92%
“…Emission rates from the H 80 center were measured on the samples used in our previous work where the H 80 level was denoted as Cu-Ni 80 . [7] Yet, only weak traces of the Cu 145 and Cu 185 centers were found after KOH:Ni treatment. These defects were located in the near-surface layer after the CP4 etching and were etched out by the long-term KOH:Ni treatment at a rather high temperature (60 °C, 40 min).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Nickel is known to be detrimental to silicon‐based electronic devices because of the extremely high diffusivity and many possible sources of nickel contamination . Recently, we showed that nickel can penetrate into silicon even at room temperatures and form complexes with radiation defects . In particular, nickel interaction with the vacancy–oxygen pair ( V O, A‐center) resulted in formation of the Ni V O complex with an acceptor level at 0.37 eV below the bottom of the conduction band.…”
mentioning
confidence: 99%